Análise do desempenho da arrecadação do ICMS dos estados brasileiros tendo em vista fatores nacionais, estaduais e idiossincráticos - Silva, Antonia Liduina Pinheiro da (2019)
This paper aimed to analyze the collecting performance of the ICMS tax in the Brazilian states during the period between 1997 and April 2019, by researching three factors that influence the collecting result. The first factor, which is common to all states, is called The National Force and affects the primary, secondary and tertiary sectors of all analyzed states. The second factor is The State Force, which affects the sectors of a specific state. The third factor is called The Idiosyncratic Force, which affects one specific sector in one specific state. Which states are the most susceptible to these forces and which states are the most unaffected? Were the results of the tax revenue better-explained by national influences or regional alterations or maybe, idiosyncratic factors? We sought to answer these questions by using the Bayesian Dynamic Latent Class-model approach, as well as the data augmentation techniques recommended by Neely and Rapach (2011) and Kose, Otrok and Whiteman (2003, 2008), which measures the degree of influence of state phenomena and national phenomena on tax revenue in each sector. In order to achieve that, we calculated the contributions made by the national factor, by the state factor, and by the idiosyncratic factor, for the total variability of ICMS-collecting, by means of the collecting-variance decomposition. The results showed that that when we check the complete period of analysis, the Idiosyncratic Force, i.e., the sector’s own features and the state’s features is the force that influences the collecting performance. However, when the total period of analysis is subdivided into two smaller periods, namely from 1997 to 2007 and from 2008 until the end of the period, the Idiosyncratic Force decreases, while the National Force increases considerably, which negatively influenced the collecting result. States with the biggest economic significance were the most affected. That means, the tax-collecting performance in states is highly susceptible to macroeconomic effects such as high inflation, high interest rates, exchange imbalances, high unemployment rate, and so forth.